1998
DOI: 10.5144/0256-4947.1998.66
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Kala-Azar Among Humans and Dogs in Yemen

Abstract: HA Al-Shamahy, Seroprevalence of Kala-Azar Among Humans and Dogs in Yemen. 1998; 18(1): 66-68 Kala-azar (visceral leishmaniasis) is a major cause of fever in the world, and is estimated to affect 100 million people worldwide.1 Kala-azar was first reported from the northern part of Yemen over 90 years ago. 2 Sporadic cases of the disease, however, are now widely reported from all over the country, including the governorates of Sana'a, Taiz, Ibb, Al-Hodeidah, Hajjah, Damar, Sa'adah, Al-Mahweet, Mareb, and Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…The prevalence of kala-azar was high in Loroo, followed by Karita and Amudat sub-counties, respectively even after stratifying by age group and sex. Although the sample size for this study was relatively small and the study not designed for risk factors assessment, the higher prevalence in Loroo and Karita sub-counties may be related to the fact that there is usually clustering of DAT positivity around active cases [13][14][15]. There were three clinical cases in Loroo and Karita compared to one in Amudat.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The prevalence of kala-azar was high in Loroo, followed by Karita and Amudat sub-counties, respectively even after stratifying by age group and sex. Although the sample size for this study was relatively small and the study not designed for risk factors assessment, the higher prevalence in Loroo and Karita sub-counties may be related to the fact that there is usually clustering of DAT positivity around active cases [13][14][15]. There were three clinical cases in Loroo and Karita compared to one in Amudat.…”
Section: Discussionmentioning
confidence: 94%
“…The ratio of symptomatic kala-azar infection to asymptomatic infection of 1:6 implies that for every symptomatic kala-azar case there are six asymptomatic kalaazar infection cases in the community. The asymptomatic cases are usually a source (reservoirs) of kala-azar infection, and thus they continue to spread the infection in the community [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn, limits the possibility of developing an effective VL control strategy. A high seroprevalence rate (34.7%; 99/285) of antibodies to Leishmania species was reported among schoolchildren from areas endemic with infantile VL in Sana’a and Hajjah governorates [ 12 ]. In addition, natural infection of feral dogs from the study areas with Leishmania species (50%; 8/16) was also documented for the first time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high seroprevalence rate (34.7%; 99/285) of antibodies to Leishmania species was reported among schoolchildren from areas endemic with infantile VL in Sana’a and Hajjah governorates [ 12 ]. In addition, natural infection of feral dogs from the study areas with Leishmania species (50%; 8/16) was also documented for the first time [ 12 ]. Haidar et al [ 13 ] reported that the clinical presentation of VL among children in Hajjah governorate, north of Yemen, is similar to that of the Mediterranean type.…”
Section: Introductionmentioning
confidence: 99%